Lysergic Acid Diethylamide, Psilocybin and Dimethyltryptamine in Depression Treatment: A Systematic Review - Gniewko Więckiewicz; Iga Stokłosa; Magdalena Piegza; Piotr Gorczyca; Robert Pudlo (MDPI AG, 2021)
Despite many different kinds of substances available for depression treatment, depression itself still appears to be a clinical challenge. Recently, formerly illicit substances came to scientists' attention, including lysergic acid diethylamide (LSD), psilocybin and dimethyltryptamine (DMT). Some studies suggest that these substances might be effective in depression treatment. The aim of this study was to evaluate the efficiency of LSD, psilocybin and DMT in depression treatment in the light of current medical literature. The authors followed the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines for this systematic review. The authors searched the PubMed and Cochrane Library databases to identify relevant publications. Finally, 10 papers were included. Most of the selected studies showed significant correlation between psilocybin and DMT use and reduction in depression symptom intensity. By analyzing qualified studies, it can be concluded that psilocybin and DMT could be useful in depression treatment, but further observations are still required.